Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan di Sumber Rejeki - Ismoyo, Faisal Dwi Wahyu (Aktualisasi Pengabdian Masyarakat, 2023)
The work environment is a place that has a big influence on employees who are carrying out work activities. The work environment provides a sense of comfort to work for employees in maintaining harmonious relationships with people who are working in the same work environment, besides that it is also accompanied by adequate infrastructure which will be able to influence employee performance properly, so as to improve employee performance. In this study the aims were to identify, describe and analyze how the influence of the work environment is considered to have a major influence on employee performance at Sumber Rejeki Company. This research method uses the method of observation, interviews, and documentation. The observation method is used to collect data by directly observing the situation and conditions in the Sumber Rejeki company area. The interview method was used to collect data and information through direct conversations with respondents using a list of questions that had been prepared previously. The population and sample here are employees who work at Sumber Rejeki Company, by interviewing 10 questions given to 10 employees with the aim of knowing how much influence the environment around the company has on employee performance at Sumber Rejeki with a quantitative method, namely correlation. The results of the study are that the work environment has a very positive effect and is directly felt by employees. It can be shown that the work environment has an effect of 90% on employee performance and 10% is influenced by other factors. The results of the research can provide information to the leadership to pay attention to the work environment because the work environment is very influential in carrying out work so that it runs effectively and efficiently.